1015. Gastrointestinal (GI) Adverse Events With Darunavir/Cobicistat/Emtricitabine/Tenofovir Alafenamide (D/C/F/TAF) Through Week 96: An AMBER Post Hoc Analysis. (31st December 2020) - Dunn, Keith; Huang, Yangxin; Baugh, Bryan; Bejou, Nika; Luo, Donghan; Campbell, Jennifer; Anderson, David
Abstract: Background: Ritonavir boosted protease inhibitors have been associated with GI intolerance. A post hoc analysis was conducted to assess the GI profile of D/C/F/TAF in treatment naïve patients. Methods: The phase 3 AMBER trial (ClinicalTrials.gov: NCT02431247) enrolled treatment naïve patients randomized 1:1 to receive once daily D/C/F/TAF 800/150/200/10 mg or D/C + F/tenofovir disoproxil fumarate (TDF). This post hoc analysis evaluated the incidence, prevalence and duration of GI adverse events of interest (AEOIs) through Wk 96. Related GI AEOIs were defined as diarrhea, nausea, abdominal pain and flatulence (by preferred term using MedDRAv21) deemed very likely, probable, or possibly related to study drug by the investigator. Incidence and prevalence were examined at weekly intervals during the first month of treatment and monthly thereafter. Duration of an AE was calculated for patients whose AEs had start and stop dates. Results: In AMBER (N = 725), 362 patients were randomized to D/C/F/TAF and 363 to D/C + F/TDF (Table ). Through Wk 48, 14% of D/C/F/TAF patients had a study drug–related GI AEOI vs 19% of D/C + F/TDF patients; of these, all were grade 1/2 and none were serious. Incidence and prevalence of D/C/F/TAF-related GI AEOIs remained low through 96 wks (Figure 1 & 2 ). Incidence of D/C/F/TAF-related diarrhea and nausea were each 5% in Wk 1 and ≤1% after Wk 2; prevalence of each decreased to < 5% at Wk 2. There was 1 case of D/C/F/TAF-related abdominal discomfort at Wk 1 and none thereafter. Incidence of D/C/F/TAF-related flatulence was < 1% from Wk 1 through Wk 96. Only 2 (1%) patients discontinued before Wk 96 due to a D/C/F/TAF-related GI AEOI (both diarrhea). Through Wk 96, < 3% of patients required treatment with concomitant medication for a D/C/F/TAF-related GI AEOI. Among patients with a D/C/F/TAF-related GI AEOI, the median duration was 16.5 days. Conclusion: In AMBER, incidences and prevalences of D/C/F/TAF-related GI AEOIs were low and tended to present early in the study. Combined with rapid decreases in prevalence, these finding suggest that GI AEOIs were transient. Overall, the GI profile of D/C/F/TAF was favorable, and to a greater extent than D/C + F/TDF, suggesting improved tolerance vs an older formulation. Table. Baseline Demographic and Clinical Characteristics Figure 1. Incidence of study drug–related GI AEOIs over time among patients randomized to D/C/F/TAF (n = 362). Figure 2. Prevalence of study drug–related GI AEOIs over time among patients randomized to D/C/F/TAF (n = 362). Disclosures: Keith Dunn, PharmD, J&J (Employee, Shareholder) Yangxin Huang, PhD, MS, J&J (Employee) Bryan Baugh, MD, J&J (Employee, Shareholder) Nika Bejou, PharmD, BCIDP, AAHIVP, J&J (Employee, Shareholder) Donghan Luo, PhD, J&J (Employee, Shareholder) Jennifer Campbell, PhD, J&J (Employee, Shareholder) David Anderson, MD, J&J (Employee, Shareholder)